Recycling Possibility of Waste Using BMP and AT4 Test - Chung, Jindo; Gong, Heyonggi (Asian Journal of Chemistry, 2014)
This study analyzed the physical and chemical properties of waste and the biodegradability to present a plan for the re-use of landfills as a basic study on the reuse of landfills. As an analysis result of physical and chemical properties, there were lots of combustible contents (50 %) compared with the analysis result of the existing landfill (30 %). The biodegradability of buried anaerobic (BMP Test) waste was analyzed to be within 11 %. As a result of the aerobic evaluation(AT4 test), the oxygen consumption of buried waste was 5.45 to 19.76 mg O2/g DM and was measured less than 2525 mg O2/g DM, a pre-stabilization evaluation standard at all the places where the sample had been collected. It seemed to be necessary to seek a plan for the reuse at landfill A by lowering the content of organic foreign materials less than 1 % through the secondary selection using the incineration treatment after drying for combustibles, the reburial for incombustibles and cleaning and wind power for sorting soil.